2023
DOI: 10.1002/cpt.2958
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Acute Effects of 2C‐B vs. Psilocybin on Subjective Experience, Mood, and Cognition

Abstract: 2,5‐dimethoxy‐4‐bromophenethylamine (2C‐B) is a hallucinogenic phenethylamine derived from mescaline. Observational and preclinical data have suggested it to be capable of producing both subjective and emotional effects on par with other classical psychedelics and entactogens. Whereas it is the most prevalently used novel serotonergic hallucinogen to date, it's acute effects and distinctions from classical progenitors have yet to be characterized in a controlled study. We assessed for the first time the immedi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Despite encouraging anecdotal human data and some academic explorations, there was little focus on drug development of 2C-X phenethylamines. However, the potential value of this series may be illustrated by the recent report showing that a psychedelic oral dose of 2C-B (20 mg) tends to produce fewer experiences of anxious ego dissolution and cognitive impairment than psilocybin; these differences support earlier drug discrimination studies in rats, wherein 2-(2,5-dimethoxy-4-(propylthio)­phenyl)­ethan-1-amine (2C-T-7) and mescaline did not fully substitute for LSD and psilocybin, , yet 2C-T-7 fully substituted for the discriminative stimulus cue of the psychedelic phenylalkylamine 1-(2,5-dimethoxy-4-methylphenyl)­propan-2-amine (DOM) …”
Section: Introductionmentioning
confidence: 56%
“…Despite encouraging anecdotal human data and some academic explorations, there was little focus on drug development of 2C-X phenethylamines. However, the potential value of this series may be illustrated by the recent report showing that a psychedelic oral dose of 2C-B (20 mg) tends to produce fewer experiences of anxious ego dissolution and cognitive impairment than psilocybin; these differences support earlier drug discrimination studies in rats, wherein 2-(2,5-dimethoxy-4-(propylthio)­phenyl)­ethan-1-amine (2C-T-7) and mescaline did not fully substitute for LSD and psilocybin, , yet 2C-T-7 fully substituted for the discriminative stimulus cue of the psychedelic phenylalkylamine 1-(2,5-dimethoxy-4-methylphenyl)­propan-2-amine (DOM) …”
Section: Introductionmentioning
confidence: 56%
“…A total of 21 studies ( n = 553) investigated memory performance under the influence of ayahuasca 79 , DOM 83 , 84 , LSA 72 , LSD 74 , 75 , 82 , 85 92 , 2C-B 93 and psilocybin 71 73 , 93 96 , utilizing 22 distinct memory tests. The majority of studies (1 LSA, 3 psilocybin, 6 LSD, 1 DOM) 72 74 , 82 , 84 , 85 , 88 90 , 95 , 96 did not show any acute effects of psychedelics on memory across fifteen tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies ( n = 503) applied 27 distinct tasks to assess the acute effects of Ayahuasca 79 , 97 , 98 , 2C-B 93 , LSD 80 , 81 , 87 89 , 99 107 , mescaline 108 and psilocybin 71 , 93 , 109 112 on executive functioning. Sixteen of the included studies (1 2C-B, 6 psilocybin, 10 LSD) 71 , 81 , 87 , 88 , 93 , 99 – 104 , 107 , 109 112 reported impaired executive functions across 19 tasks, while twelve studies (2 psilocybin, 3 ayahuasca, 7 LSD) 71 , 79 , 80 , 87 , 89 , 97 99 , 101 , 105 , 106 , 111 reported no effects across 15 tasks. Additionally, five studies (2 ayahuasca, 2 LSD, 1 mescaline) 79 , 97 , 99 , 101 , 108 showed improved performance across six tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from clinical trials on the therapeutic use of mescaline are scarce. A recent study compared the immediate acute subjective, cognitive, and cardiovascular effects of 2,5-dimethoxy-4-bromophenethylamine (2C-B), a mescaline-derived hallucinogenic phenethylamine, with psilocybin in a group of 11 women [134]. The participants were given 20 mg of 2C-B, 15 mg of psilocybin, or a placebo on three separate occasions.…”
Section: Mescalinementioning
confidence: 99%